THE ANALYSIS OF GRAMMATICAL COHESIVE DEVICES IN THE EIGHTH GRADE STUDENTS’ WRITING OF SMP N 1 SINGARAJA - ., I Komang Oka Agustiyana; ., Prof. Dr. Anak Agung Istri Ngr. Marha; ., Ni LP. Eka Sulistia Dewi, S.Pd. M.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujuan untuk mengidentifikasi tipe-tipe Grammatical Cohesive Devices dan Error yang ditemukan dalam karangan Recount siswa kelas delapan SMP N 1 Singaraja. Karangan siswa dianalisa menggunakan teori Halliday dan Hasan (1976). dalam jumlah terbatas, sejumlah enam belas karangan Recount siswa dianalisis dalam penggunaan grammatical cohesive devices. Terdapat 339 penggunaan grammatical cohesive devices dalam karangan siswa. Siswa sebagian besar menggunakan Conjunction (Kata Pennghubung) dalam karangan recount untuk membuat karangan yang cohesive. Penggunaan kata penghubung merupakan yang terbayak. Sebesar 49.85%, dengan penggunaan sebanyak 169 penggunaan. Penggunaan Reference (Kata Acuan) sebesar 41.30% atau 140 temuan penggunaan. Penggunaan Ellipsis (Elipsis) sebesar 8.85%, atau 30 kali penggunaan. Namun demikian, penggunaan Substitution (Substitusi) tidak ditemukan penggunaannya dalam karangan siswa. Hasil temuan menunjukkan dari 339 penggunaan, 94.40% atau 320 penggunaan grammatical cohesive devices digunakan dengan tepat. Sedangkan 5.60% atau 19 error ditemukan dalam karangan Recount siswa. Error yang ditulis oleh siswa berupa penggunaan Reference 47.37%, atau sebanyak 9 penggunaan. Error dalam penggunaan Ellipsis dan Conjunction masing-masing 5 penggunaan yang sebanding dengan 52.63%.Kata Kunci : reference, substitution, ellipsis, conjunction, grammatical cohesive devices The purposes of the study were to identify kinds of grammatical cohesive devices and errors found in the eighth grade students’ recount writing of SMP N 1Singaraja. The analysis was based on Halliday and Hasan’s theory (1976). There were sixteen students’ recount writings analyzed restrictively on the grammatical cohesive devices use. There were 339 grammatical cohesive devices occurrences found in the students’ writing. The students used Conjunction dominantly in Recount to create cohesion in their writing. The use of conjunction was the biggest one. It was 49.85%, with 169 occurrences. The use of reference was 41.30%, or 140 occurrences. The use of ellipsis was found 8.85%, or 30 occurrences. However, the use of Substitution was not found in the students’ writing. The results of the findings show from the 339 occurrences, the appropriately used grammatical cohesive devices are 94.40% or 320 occurrences. Meanwhile, there are 5.60% or 19 errors appeared on the students’ recount writing. The errors are produced in the use of Reference 47.37%, or equal to 9 occurrences. The error use of Ellipsis and Conjunction contribute 5 errors each which are equal to 52.63%.keyword : reference, substitution, ellipsis, conjunction, grammatical cohesive devices